Policy and governance in tourism: A perspective from the circular economy in Tabasco, Mexico - Rojas Carranco, Violeta Guadalupe; Mazó Quevedo, María Lyssette; Ortiz Martínez, Fabiola Itzel; De la Cruz Rojas, Edgar Andrés (Revista Colombiana de Ciencias Sociales, 2025)
This article examines public policy applied within the tourism sector of Tabasco, Mexico, with the objective of identifying the inclusion of criteria associated with the circular economy across thirteen municipalities in the state. The analysis focuses on the extent to which these criteria emerge from active citizen participation in policy planning and governmental action, rather than from citizens acting merely as spectators or executors of policies disconnected from their lived reality. The qualitative design is grounded in an analysis of academic literature and municipal public policy documents addressing governance and circular economy issues. Subsequently, a matrix containing twelve indicators was developed to evaluate the three categories. Among the findings, it was observed that the thirteen municipal development plans do not comprehensively integrate elements related to governance, tourism, and the circular economy. Moreover, although some municipalities did consider these three concepts during the planning of public policy, the study concludes that, overall, local governments could work in a more coordinated and coherent manner in implementing these constructs to advance toward a circular economy model in rural tourism destinations.